2010
DOI: 10.1016/j.ijfoodmicro.2009.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Campylobacter populations isolated from a free-range broiler flock before and after slaughter

Abstract: Relatively little is known about the Campylobacter genotypes colonizing extensively reared broiler flocks and their survival through the slaughter process, despite the increasing demand for free-range and organic products by the consumer. Campylobacter isolates from a free-range boiler flock, sampled before and after slaughter, were genotyped by MLST (multilocus sequence typing) and sequence analysis of the flaA short variable region (SVR). The Campylobacter genotypes isolated before and after slaughter were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
7
22
0
Order By: Relevance
“…The presence of multiple Campylobacter strains ( 6 ) in individual outbreaks linked to chicken liver is consistent with documentation that chickens harbor multiple strains ( 8 ), that pâté is prepared from multiple livers ( 5 , 6 ), or both. We describe epidemiologic evidence for a duck liver pâté–associated outbreak and compare sequence types (STs) of isolates with animal and food isolate datasets.…”
supporting
confidence: 80%
“…The presence of multiple Campylobacter strains ( 6 ) in individual outbreaks linked to chicken liver is consistent with documentation that chickens harbor multiple strains ( 8 ), that pâté is prepared from multiple livers ( 5 , 6 ), or both. We describe epidemiologic evidence for a duck liver pâté–associated outbreak and compare sequence types (STs) of isolates with animal and food isolate datasets.…”
supporting
confidence: 80%
“…This observation is supported by a recent study from the United Kingdom where the predominant strains in poultry flocks were also the predominant strains found on the final carcass (12), but it is in contrast to other studies where differential survival of genotypes was observed (13,14).…”
supporting
confidence: 76%
“…Statistical analysis indicated that this is a highly significant association and that the majority of samples obtained from the neck skin originated from the slaughtered flock itself. Given the fact that only single colonies were analyzed and that both species and various genotypes can be present in the flock, the true number of self-contaminated carcasses can be quite large (5,52). The remaining nonmatching isolates that were obtained from the neck skin could have come from other contaminated sources, such as previously slaughtered batches, equipment, working surfaces, or water (19,36,49).…”
Section: Discussionmentioning
confidence: 99%